2019
DOI: 10.1186/s12889-019-6392-2
|View full text |Cite
|
Sign up to set email alerts
|

The association between ethnicity, stigma, beliefs about medicines and adherence in people living with HIV in a rural area in Indonesia

Abstract: BackgroundIndonesia is one of Asia’s countries with the fastest growing rate of human immunodeficiency virus (HIV) infections according to the World Health Organization (WHO). The prevalence of HIV infections in the province of Papua is 2.4% which is 24 times higher than the national rate in Indonesia. This study aimed to investigate the association between stigma, beliefs about medicines, sociodemographic characteristics including ethnicity and adherence in People living with HIV (PLHIV) in Papua, Indonesia.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…2 Previous survey-based studies in Papua showed low levels of health literacy, 24 and lower levels of adherence to medication than in other parts of Indonesia. 25 We also found that enacted stigma was significantly associated with non-adherence among Papuans. 26 To improve the situation for Papuans living with HIV, more in-depth knowledge is needed on barriers and facilitators to access medication and remain on treatment in particular in the changing organisation of healthcare taking into account the local culture.…”
Section: Introductionmentioning
confidence: 54%
“…2 Previous survey-based studies in Papua showed low levels of health literacy, 24 and lower levels of adherence to medication than in other parts of Indonesia. 25 We also found that enacted stigma was significantly associated with non-adherence among Papuans. 26 To improve the situation for Papuans living with HIV, more in-depth knowledge is needed on barriers and facilitators to access medication and remain on treatment in particular in the changing organisation of healthcare taking into account the local culture.…”
Section: Introductionmentioning
confidence: 54%
“…HIV, leprosy, schizophrenia, and diabetes. These four conditions were purposively chosen because of their diverse nature and etiology (infectious vs non-communicable), and causes of stigmatization in the Indonesian society [36][37][38][39]44].…”
Section: Methodsmentioning
confidence: 99%
“…It also has high prevalence of noncommunicable health conditions like diabetes mellitus (6.7% in adults) [33] and schizophrenia (around 1%) [34]. Besides the high burden, these four health conditions are also stigmatized in the Indonesian society because of the prevalent social norms, and associated negative stereotypes and misinformation [35][36][37][38][39].…”
Section: The Context Of Indonesiamentioning
confidence: 99%
“…Few studies have reported the negative experiences of stigma among people with HIV, [29][30][31][32][33][34] and leprosy. 3,4,11,[35][36][37] in Indonesia.…”
Section: Introductionmentioning
confidence: 99%